(untitled) (Research, Society and Development, 2022)
The study aimed to analyze the financial feasibility of implementing robotic milking on a dairy farm in western Santa Catarina/Brazil. This is a descriptive case study with a qualitative basis using semi-structured interviews. Based on cost measurement for implementation of robotic milking in the period of activity of 2022, a comparative analysis was made of the incremental cash flow relative to a transition from conventional to robotic milking. One of the major findings is that the simple payback time is approximately 4.9 years while the discounted payback period is approximately 5.11 years, considering a MARR of 10% as the expected profit per year. The implementation of robotic milking yields an IRR of 28.79%. It was also found that accounting is an important instrument for planning resources and investments for activities developed in rural settings, thus enabling short and long-term planning.